BRCA-mutated gastric adenocarcinomas are associated with chromosomal instability and responsiveness to platinum-based chemotherapy - Ji Hyun Oh; Chang Ohk Sung; Hyung-Don Kim; Sung-Min Chun; Jihun Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Background Homologous recombination defect is an important biomarker of chemotherapy in certain tumor types, and the presence of pathogenic or likely pathogenic mutations involving BRCA1 or BRCA2 (p-BRCA) mutations is the most well-established marker for the homologous recombination defect. Gastric cancer, one of the most prevalent tumor types in Asia, also harbors p-BRCA mutations. Methods To investigate the clinical significance of p-BRCA mutations, we analyzed 366 gastric cancer cases through next-generation sequencing. We determined the zygosity of p-BRCA mutations based on the calculated tumor purity through variant allelic fraction patterns and investigated whether the presence of p-BRCA mutations is associated with platinum-based chemotherapy and a certain molecular subtype. Results Biallelic p-BRCA mutation was associated with better response to platinum-based chemotherapy than heterozygous p-BRCA mutation or wild type BRCA genes. The biallelic p-BRCA mutations was observed only in the chromosomal instability subtype, while all p-BRCA mutations were heterozygous in microsatellite instability subtype. Conclusions In conclusion, patients with gastric cancer harboring biallelic p-BRCA mutations were associated with a good initial response to platinum-based chemotherapy and those tumors were exclusively chromosomal instability subtype. Further investigation for potential association with homologous recombination defect is warranted.